Structural analysis of affect in the pre-purchase context - Seva, Rosemary R. (Animo Repository, 2010)
Previous studies on consumption related affect did not identify specific components in the pre-purchase context. This article reviewed theoretical bases of affect and its relationship to product judgment and determined the components and structure of pre-purchase affect. Field studies were conducted to gather an initial list of affect experienced before purchasing "high-involvement" products. An initial list of 94 pre-purchase affect was identified and trimmed down to 18 after further statistical analysis. A second study was conducted to determine the structure of the pre-purchase emotion set (PES) derived from the first study. Multidimensional scaling was used and four clusters of emotion were found labeled satisfaction, positive enthusiasm, optimism, and amazement. The same results were found using factor analysis. It was proposed that pre-purchase affect experience followed the human information processing model. © 2010 De La Salle University, Manila, Philippines.